Synthesis of crystalline Mo–V–W–O complex oxides with orthorhombic and trigonal structures and their application as catalysts. (April 2015) - Qiu, Chuntian; Chen, Chen; Ishikawa, Satoshi; Zhang, Zhenxin; Murayama, Toru; Ueda, Wataru
Abstract : Crystalline Mo–V–W–O complex oxides with the orthorhombic or trigonal structure were synthesized by a hydrothermal method. Those Mo–V–W–O samples with various amounts of tungsten were characterized by inductively coupled plasma atomic emission spectroscopy, TEM, STEM–EDX, X-ray diffraction, Rietveld analysis, and a N2 adsorption method. It was found for the first case that an additional metal such as W can be successfully incorporated into the trigonal Mo–V–O structure by using (CH3 CH2 NH3 )2 Mo3 O10 .The alkylammonium cation acted as a structural stabilizer that was requisite for the formation of a trigonal structure when additional metal ions were present. For the orthorhombic Mo–V–W–O structure, introduction of W into the orthorhombic structure caused a rod segregation effect by which nanoscale crystals formed and the external surface area greatly increased. Additionally, these Mo–V–W–O materials were applied as catalysts for the gas phase selective oxidation of acrolein to acrylic acid. The best catalyst was assigned to the orthorhombic Mo–V–O–W7.5, which possessed an ordered arrangement of heptagonal and hexagonal channels and a large external surface area.